Maternal Mortality: 10 Year Experience of a Tertiary Center in Turkey. (30th September 2020) - Fadiloglu, Erdem; Unal, Canan; Tanacan, Atakan; Ocal, Serpil; Kilicaslan, Banu; Akinci, Seda Banu; Topeli, Arzu; Beksac, M. Sinan
Abstract : We retrospectively evaluated five maternal mortality cases that occurred in our institution within the last 10 years. Rate of maternal mortality was 24.5 per 100000 live births. Maternal mortality causes were cardiopulmonary failure secondary to veno-occlusive disease, septic shock secondary to osteosarcoma, pulmonary thromboembolism secondary to metastatic breast cancer, septic shock secondary to cholecystitis, and postpartum hemorrhage secondary to Niemann–Pick disease. Four out of five cases were evaluated as indirect maternal mortality cases. Three out of five cases ended up with a healthy newborn, while other cases ended up with abortus and postpartum exitus.